Geologi Daerah Lebaksiuh dan Sekitarnya, Kecamatan Jatigede, Kabupaten Sumedang, Propinsi Jawa Barat - Ratih C F Ratumanan; Diana Porsisa; Sri Indriaty; Rimawanto Gultom; Ronald D Hukubun (Yayasan Literasi Sains Indonesia, 2025)
Administratively, the research area is located within the Lebaksiuh Region and its surroundings, Jatigede District, Sumedang Regency, West Java Province. The method used in this study is geological mapping. The research area is divided into five geomorphological units: the Steep Intrusive Geomorphology Unit, the steep structural hill unit, Gently to moderately steep structural hills, the moderately structural hill unit, and denudational unit. Based on the stratigraphy units, the research area is subdivided into three rock units: the carbonate sandstone unit (Tobpk), the tuffaceous sandstone unit (Tpbp), and the intrusive unit (a). The geological structures developed in the study area include folds, joints, and faults. The geological history of the area shows that during the late oligocene–early miocene, the carbonate sandstone unit (Tobpk) was deposited in a bathyal depositional environment. Subsequently, unconformably, the sandstone unit (Tpbp) was deposited during the pliocene in a fluvial environment. The depositional process was later interrupted by tectonic activity during the pleistocene, characterized by compressional tectonics that formed a series of geology structure trending northwest–southeast. Tectonic activity also led to the formation of joints and faults in the study area, as well as volcanic activity that produced intrusions along zones of weakness. The geological resources and hazards identified in the research area include potential mineral resources and geotourism potential, particularly at the Cisempong Waterfall.